JAVA DELI (JADEL) WOMEN'S CONTESTATION IN THE STRUCTURE OF THE PATRIARCHY SOCIETY IN THE DELI OF NORTH SUMATERA - Leylia Khairani (Proceeding International Seminar of Islamic Studies, 2021)
This research aims to see how the position of the Java Deli women in the structure of the patriarchal society in North Sumatra which was formed from the socio-cultural world of plantations. The method used is the literature method by triangulating sources through interviews. The results presented in this paper show that plantation life has positioned Deli Javanese women to be subordinated and marginalized so that they have an impact on stigmatizing their domestic and reproductive roles. Keywords: Java Deli, Contestation, Women, Plantation, Patriarchy